The political vision of Europe during the 'refugee crisis': missing common ground for integration. Issue 1 (2nd January 2018) - Wolf, Marie; Ossewaarde, Marinus
Abstract: This article analyses imaginaries of political decision makers of the European Union in the context of the 'refugee crisis' and interprets them according to theories of European integration – neofunctionalism and liberal intergovernmentalism. Speeches, interviews, statements and press releases of the 28 heads of state and government and two Commissioners are analysed through a qualitative content analysis. The aim of the article is to derive prospects for European integration from the imaginaries. We found that the European imaginaries expressed by the largest group of heads of state and government remain blurred without clarification which position is taken on European integration, while the imaginaries expressed by the Commissioners are mainly characterised by support of further integration. Our interpretation of the European imaginaries suggests that the prospects for further integration remain limited according to neofunctionalism, but are higher following liberal intergovernmentalism. In policy fields that are directly related to the management of the crisis further cooperation can be expected.